PRODUKSI ENZIM INVERTASE OLEH SACCHAROMYCES CEREVISIAE MENGGUNAKAN SUBSTRAT GULA DENGAN SISTEM FERMENTASI CAIR - Argadenta Adi Prabawa; Emil Hanityo Utomo; A. Abdullah (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Sugar is one of simple carbohydrates that act as source of primary energy and popular commodity trading. Sugar most widely traded in the form of crystalline solid sucrose. The addition of sucrose in the media serves as a carbon source. The purpose of this study was to produce the invertase enzyme, Assessing the impact of substrate concentration and nitrogen source on the production of invertase, and establish optimum conditions for production of the invertase enzyme. In this study the method used is a liquid fermentation systems. Research carried out in erlenmeyer with fixed variables, among other nutrients in the media (MgSO4.7H2O KH2PO4 0.5 mg and 2.3 mg), fermentation temperature of 30oC, fermentation pH 4.5 and within 48 hours and media were incubated in an incubator Secker . The variables changed in this study is the concentration of sucrose, among others, 100; 125; and 150 g / L and the concentration of N sources, including 2.6; 3.2, and 3.8 g / L. The results of fermentation was separated by centrifugation to obtain the invertase enzyme, then the protein levels were analyzed by the Lowry’s method and enzyme activity were tested using the method of DNS (3,5-dinitrosalicylic acid). The experimental results showed that sugar substrates can be used to produce the invertase enzyme by Saccharomyces cerevieae with protein levels of 5.309 mg / L and the resulting enzyme activity 0.05916 mmol / L.minute. The most optimum enzyme activity is achieved at a concentration of sucrose and nitrogen sources are sufficient (125 g / L and 3.2 g / L).